From Ritual to Content: The Mediatization of Dhikr, Duʿa, and Symbolic Participation in Digital Islam - Derry Ahmad Rizal; Moh Syaiful Bahri (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
This article examines how Islamic ritual practices, particularly dhikr and duʿa (supplication), are mediated, represented, and transformed into digital content on platform-based media. Employing an interpretive qualitative approach and a lived religion perspective, this study analyzes publicly available digital media artifacts from the Instagram and TikTok accounts of Hanan Attaki and Halimah Alaydrus. The research corpus comprises 32 video posts, 32 post captions, and 640 audience comments, which were examined using qualitative content analysis and interpretive thematic analysis. The findings demonstrate that dhikr and duʿa are reconfigured into short-form audiovisual content through temporal compression, the foregrounding of visual expression, the use of affective textual cues, and the amplification of emotional resonance. Audience interactions, including comments containing duʿa, emojis, affective expressions, and devotional responses, were interpreted as patterns of distributed and asynchronous symbolic ritual participation. In addition, repeated visibility and audience recognition of ritual content contribute to the formation of platform-based religious authority. This article contributes to the study of the mediatization of religion, ritual studies, and lived Islam by positioning ritual practices as a primary analytical site within digital Islam. This study affirms that digital media do not merely serve as channels for the dissemination of religion but also shape how rituals are produced, encountered, and recognized in contemporary Muslim life.